2013
DOI: 10.4238/2013.february.28.16
|View full text |Cite
|
Sign up to set email alerts
|

Association between adipose tissue expression and serum levels of leptin and adiponectin in women with polycystic ovary syndrome

Abstract: ABSTRACT. We reviewed emerging evidence linking serum levels and adipose tissue expression of leptin and adiponectin in women with polycystic ovary syndrome (PCOS). Previous data obtained by our group from a sample of overweight/obese PCOS women and a control sample of normal weight controls, both stratified by BMI, were reanalyzed. Circulating levels of leptin and adiponectin were determined by commercially available enzyme-linked immunosorbent assays. Adipose tissue total RNA was reserve-transcripted into co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…As previously reported by us, leptin gene expression was higher in SC fat of overweight/ obese PCOS in comparison with normal-weight controls. In contrast, adiponectin gene expression did not differ between obese and non-obese subgroups (Lecke et al 2011a(Lecke et al , 2013b. These data are in agreement with other reports regarding PCOS and control populations (Wang et al 2012).…”
Section: Leptin and Adiponectinsupporting
confidence: 82%
See 2 more Smart Citations
“…As previously reported by us, leptin gene expression was higher in SC fat of overweight/ obese PCOS in comparison with normal-weight controls. In contrast, adiponectin gene expression did not differ between obese and non-obese subgroups (Lecke et al 2011a(Lecke et al , 2013b. These data are in agreement with other reports regarding PCOS and control populations (Wang et al 2012).…”
Section: Leptin and Adiponectinsupporting
confidence: 82%
“…While our group and other authors found similar circulating adiponectin levels in BMI-matched PCOS and control women (Lecke et al 2011a, 2013b, Pepene 2012, Tan et al 2013, other studies have reported lower adiponectin levels in PCOS women in comparison with healthy controls, independently of BMI: a meta-analysis including more than 3500 subjects (PCOS women and healthy BMI-matched controls) of various ages with different levels of total testosterone and insulin found that adiponectin was significantly lower in PCOS (Li et al 2014). Reduced adiponectin levels appear to play a role in promoting insulin resistance increasing triglycerides and small and dense LDL particles (Tan et al 2006a).…”
Section: Leptin and Adiponectinmentioning
confidence: 79%
See 1 more Smart Citation
“…The association between altered adiponectin levels and PCOS remains controversial, with some studies reporting comparable adiponectin levels in BMI-matched PCOS and control women (11,12,17), and others (8,9,11,16), including two meta-analyses (18,19), showing that women with PCOS have lower levels of adiponectin independent of body mass index (BMI).…”
mentioning
confidence: 98%
“…Also, PCOS is associated with obesity, central adiposity, and dyslipidemia (3)(4)(5), and an increased risk of type 2 diabetes (T2DM) (1,5,6), which have been linked to insulin resistance (IR) (7,8). Insofar as adipose tissue secretes bioactive cytokines and adipokines, including adiponectin, leptin, and resistin (9), mounting evidence implicates dysregulated adipokine expression with the onset of obesity-related pathologies including PCOS (9)(10)(11)(12).…”
mentioning
confidence: 98%